The Relationship Between Nurse Supervision With Compliance Toward Handover During The Pandemic COVID-19 in Indonesia - Dudi Mauludin; Lia Idealistiana (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims : Knowing the optimization of the implementation of supervision on nursing handover compliance. Methods : Analytical with cross sectional. The sample in this study were 51 nurses in the inpatient room, the sampling technique was Total Sampling. Results : Of the 51 respondents most of the respondents carried out supervision as many as 45 people (88.2%) and 6 people did not carry out supervision (11.8%). Based on compliance, most of the compliant did handovers as many as 43 people (84.3%) and those who did not comply with handovers as many as 8 people (15.7%). There was a significant relationship between the implementation of supervision and handover compliance (p value 0.006). Conclusions : There is a significant relationship between the implementation of supervision and handover compliance so as to obtain optimal results. It is hoped that there will be solid cooperation between the head of the room and the implementing nurse so that it can produce good performance.